2019
DOI: 10.1039/c9md00122k
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and microbiological evaluation of N-aryl urea derivatives against mycobacteria and mycobacterial hydrolases

Abstract: N-Aryl urea derivatives were synthesized and some showed activity against mycobacterial hydrolases while others showed antimicrobial activity against mycobacterial species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Only the 4e compound, shown in Table 2, exhibited a moderate MIC of 25 µM, while the toxicity analysis performed over murine cells showed a higher MIC. Despite these preliminary results, this study is a valuable starting point for the development of effective Mab hydrolase inhibitors [62]. Another important target involved in cell wall biosynthesis is the enoyl-ACP reductase (InhA), which is involved in mycolic acid biosynthesis [64].…”
Section: Other Inhibitors Of the Cell Wall Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…Only the 4e compound, shown in Table 2, exhibited a moderate MIC of 25 µM, while the toxicity analysis performed over murine cells showed a higher MIC. Despite these preliminary results, this study is a valuable starting point for the development of effective Mab hydrolase inhibitors [62]. Another important target involved in cell wall biosynthesis is the enoyl-ACP reductase (InhA), which is involved in mycolic acid biosynthesis [64].…”
Section: Other Inhibitors Of the Cell Wall Metabolismmentioning
confidence: 98%
“…Rv3802c belongs to a gene cluster that modulates mycolic acid biosynthesis and transport. Recent studies have confirmed that this enzyme hydrolyses the phosphatidylinositol, regulating the membrane lipid content [62]. Considering the importance of his role in cells, Rv3802c has been taken into consideration as a putative drug target to kill mycobacteria.…”
Section: Other Inhibitors Of the Cell Wall Metabolismmentioning
confidence: 99%
“…We synthesized derivative FAM-DA-3CH2 in two steps (Scheme ). At first, alkyne 1 was obtained from furfuryl isocyanate, which is commercially available or otherwise readily accessible from furfurylamine . Second, using the Hay catalyst, we achieved the homocoupling reaction of the terminal alkyne 1 in 2 h 30 min to give the desired diacetylene.…”
Section: Synthesismentioning
confidence: 99%
“…An independent research group reported on the activity of an N ‐aryl urea derivative (structures not shown) against M. abscessus (MIC value of 25 µM) but the mechanism through which the compound inhibits mycobacterial growth was not determined 192 …”
Section: Interesting Early‐stage Small Molecules Active Against M Abscessus: From Bench To Bedside?mentioning
confidence: 99%